HER-3 peptide vaccines/mimics: Combined therapy with IGF-1R, HER-2, and HER-1 peptides induces synergistic antitumor effects against breast and pancreatic cancer cells - Miller, Megan Jo (Oncoimmunology, 2014)
The human epidermal growth factor receptor 3 (HER-3/ErbB3) is a unique member of the human epidermal growth factor family of receptors, because it lacks intrinsic kinase activity and ability to heterodimerize with other members. HER-3 is frequently upregulated in cancers with epidermal growth factor receptor (EGFR/HER-1/ErbB1) or human epidermal growth factor receptor 2 (HER-2/ErBB2) overexpression, and targeting HER-3 may provide a route for overcoming resistance to agents that target EGFR or HER-2. We have previously developed vaccines and peptide mimics for HER-1, HER-2 and vascular endothelial growth factor (VEGF). In this study, we extend our studies by identifying and evaluating novel HER-3 peptide epitopes encompassing residues 99–122, 140–162, 237–269 and 461–479 of the HER-3 extracellular domain as putative B-cell epitopes for active immunotherapy against HER-3 positive cancers. We show that the HER-3 vaccine antibodies and HER-3 peptide mimics induced antitumor responses: inhibition of cancer cell proliferation, inhibition of receptor phosphorylation, induction of apoptosis and antibody dependent cellular cytotoxicity (ADCC). Two of the HER-3 epitopes 237–269 (domain II) and 461–479 (domain III) significantly inhibited growth of xenografts originating from both pancreatic (BxPC3) and breast (JIMT-1) cancers. Combined therapy of HER-3 (461–471) epitope with HER-2 (266–296), HER-2 (597–626), HER-1 (418–435) and insulin-like growth factor receptor type I (IGF-1R) (56–81) vaccine antibodies and peptide mimics show enhanced antitumor effects in breast and pancreatic cancer cells. This study establishes the hypothesis that combination immunotherapy targeting different signal transduction pathways can provide effective antitumor immunity and long-term control of HER-1 and HER-2 overexpressing cancers.